2016
DOI: 10.1016/j.cardfail.2016.02.007
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effectiveness of Tolvaptan in Patients With Acute Heart Failure and Renal Dysfunction

Abstract: URL: http://www.umin.ac.jp/ctr/index/htm/ Unique identifier: UMIN000007109.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(134 citation statements)
references
References 35 publications
2
126
4
2
Order By: Relevance
“…Previous studies of TLV use were tested in acute HF without accounting for diuretic resistance. [8][9][10][11] There are 3 main findings of the present study. First, additive TLV resulted in significantly higher UV than increased FUR, primarily through increased urinary water excretion in HF patients with residual congestion despite concomitant FUR.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies of TLV use were tested in acute HF without accounting for diuretic resistance. [8][9][10][11] There are 3 main findings of the present study. First, additive TLV resulted in significantly higher UV than increased FUR, primarily through increased urinary water excretion in HF patients with residual congestion despite concomitant FUR.…”
Section: Discussionmentioning
confidence: 52%
“…It is possible that adequate fluid control can be achieved with TLV administration alone, without the need for large amounts of loop diuretics, and TLV administration might prevent the induction of renal impairment by loop diuretics. 7,8) Worsening renal function in heart failure is a prognostic factor: We have often observed impaired renal function occurring during hospitalization in patients with acute HF, so called WRF. 9,10) A considerable number of patients admitted with ADHF have significant renal impairment, which influences treatment and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported an add-on effect of TLV in patients with ADHF and renal dysfunction. 8) The TLV group showed more diuresis than the conventional group (6464.4 versus 4999.2 mL, P < 0.001) despite significantly lower loop diuretic doses (80 mg versus 120 mg, P < 0.001). However, the rate of WRF was not different between TLV and conventional groups (24.1% versus 27.8%, respectively; P = 0.642).…”
Section: And Prognosis In Acute Heart Failurementioning
confidence: 99%
“…Patients with worsening renal function are often encountered during the treatment of ADHF. Previous studies also reported that TLV alleviated renal dysfunction while treating ADHF, so TLV is a useful medication for treatment of patients with ADHF and renal dysfunction (2,13). In addition, serum sodium levels must be cautiously monitored because TLV was developed as a medication to treat hyponatremia (14).…”
Section: The Severity Of Heart Failure In Subjectsmentioning
confidence: 99%